2020
DOI: 10.1002/jts.22596
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐Based Writing Therapies for Subthreshold and Clinical Posttraumatic Stress Disorder: A Systematic Review and Meta‐Analysis

Abstract: We undertook a systematic review to assess the efficacy of exposure‐based writing therapies (WTs) for trauma‐exposed adults with subthreshold or clinical levels of posttraumatic stress disorder. Four databases (PsycINFO, Medline, Wiley Online, PILOTS) were searched for randomized controlled trials (RCTs) of exposure‐based WTs. A total of 13 RCTs that reported on results from 17 WT versus control comparisons were included. The primary outcomes were posttraumatic stress symptom severity at posttreatment and/or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
(113 reference statements)
0
10
0
Order By: Relevance
“…We thank Thompson‐Hollands et al. (2020) for their thoughtful commentary on our recent systematic review, which explored the efficacy of exposure‐based writing therapies (WTs) for posttraumatic stress symptoms (PTSS; Dawson et al., 2020). The points raised in the commentary highlight the challenges of integrating evidence about the efficacy of an emerging therapeutic technique that is grounded in and translated from various conceptual positions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We thank Thompson‐Hollands et al. (2020) for their thoughtful commentary on our recent systematic review, which explored the efficacy of exposure‐based writing therapies (WTs) for posttraumatic stress symptoms (PTSS; Dawson et al., 2020). The points raised in the commentary highlight the challenges of integrating evidence about the efficacy of an emerging therapeutic technique that is grounded in and translated from various conceptual positions.…”
mentioning
confidence: 99%
“…Advantages of broad reviews are that they allow for the exploration of the consistency of findings across participant populations and different implementations of an intervention (Thomas et al., 2020). Our review identified four types of WTs (see Supplementary Table S4 of Dawson et al., 2020). To make recommendations for future research, we planned to perform subgroup analyses to explore different characteristics of the WT interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Having conducted several of the studies included in Dawson and colleagues’ (2020) recently published meta‐analytic review of exposure‐based writing interventions for posttraumatic stress disorder (PTSD), we read the results with great interest. Their findings indicated that exposure‐based writing interventions are more efficacious than both waitlist and placebo writing control conditions.…”
mentioning
confidence: 99%
“…Combining the outcomes of the expressive writing studies as done by Dawson et al. (2020) obscures these important methodological differences across studies.…”
mentioning
confidence: 99%